Impacto del régimen impositivo para microempresas en el sector comercial de la ciudad de Machala 2020-2021 - Peñafiel Eugenio, Laura Salome; Zaruma Villon, Hilda Beatriz (Universidad Técnica de Machala, 2022)
The developed research aims to determinate the impact of Tax Regime for Micro-enterprises related to the payment of income tax for small businesses located in Machala city, through the implementation of a descriptive investigation about the implicit facts during the 2020-2021 period, taking as a research basis a non-experimental design due to it is developed in a natural context with a quantitative approach worked with statistical data that allow a measurement of the background information collected and the sample considered for the execution of the study was taken from a subgroup of taxpayers selected through the stratified sampling technique, applying a survey with dichotomous questions related to the case study to find out how taxpayers were affected by entering the regime. It is essential to mention that from the year 2019 the country went through a health emergency, and as a result of what happened the merchants had difficulties for the continuous development of their activities, affecting business liquidity and availability of payments. Causing the majority of taxpayers were severely affected by the calculation of 2% of their net income at the time of declaring the income tax, due to the costs and expenses generated by the activity were not considered and for the impediment of the use of the tax credit of previous fiscal years. Nevertheless, it was until the first half of 2021 that the credit box from previous years was added, where those taxpayers who only had one activity made use of it. It is notable that the taxpayers enjoy tax benefits but not all of them have the necessary knowledge to apply them or they are not kept informed about the implemented reforms, being so helpful the participation of an accounting professional and the encouragement of the tax culture oriented to guide the taxpayers to stay informed about the resolutions that are issued through the Internal Revenue Service’s Portal.
El presente trabajo, tiene como objetivo determinar el Impacto del Régimen Impositivo para Microempresas en el pago del Impuesto a la Renta de los pequeño negocios comerciales de la ciudad de Machala, a través de la implementación de una investigación descriptiva de los hechos implícitos durante el período 2020-2021, tomando como base de investigación un diseño no experimental al desarrollarse en un contexto natural, y con enfoque cuantitativo al trabajarse con datos estadísticos que permitan realizar una medición de los antecedentes recogidos, y la muestra considerada para la ejecución del estudio fue tomada de un subgrupo de contribuyentes seleccionado por medio de la técnica de muestreo estratificado, aplicando así una encuesta dicotómica con preguntas afines al caso de estudio para conocer como afectó la inserción al régimen a los contribuyentes. Es menester mencionar que a partir del año 2019 el país atravesó una emergencia sanitaria, y a raíz de lo sucedido los comerciantes tuvieron dificultades para el desarrollo continuo de sus actividades, afectando la liquidez de negocio y disponibilidad de pagos. Causando que mayor parte de los contribuyentes se vieran gravemente afectados por el cálculo del 2% de sus ingresos netos al momento de declarar el impuesto a la renta, debido a que, no se consideraban los costos y gastos generados por la actividad y por el impedimento del uso crédito tributario de ejercicios anteriores. No obstante, fue hasta el año 2021 en el primer semestre que se adicionó el casillero de créditos tributarios de ejercicios anteriores, donde aquellos contribuyentes que solo contaban con una actividad económica hacían uso del mismo.
Keywords: IMPUESTO A LA RENTA; BENEFICIOS TRIBUTARIOS; EGIMEN IMPOSITIVO PARA MICROEMPRESAS; CONTRIBUYENTE